¿Sangre azul en números rojos? La participación de la nobleza de Amberes en el mercado de censales (1490-1493) (Edad Media. Revista de Historia, 2018)
This article investigates the activities of noblemen on the annuity market of the city of Antwerp at the end of the fifteenth century. In postwar historiography, the consumption of credit by noblemen was often considered as an indication that those noblemen were in dire straits, whereas more recent interpretations suggest that noblemen were important creditors to both princes and towns. The analysis of the activities of twenty-eight noble lineages on the Antwerp credit market reveals that noblemen appear more often as buyers than as sellers of credit, but also that they were considered creditworthy, and that noblemen were careful to avoid using estates that were important for the family’s noble status as collateral. The nobility's annuity traffic cannot be understood from a one-sided perspective, such as that of the overarching grand narrative of the perpetual crisis of the pre-modern nobility, or that of the nobleman-banker.
Keywords: Antwerp; City; Nobility; Capital; Capital Markets